(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In our independent Uzbekistan, due to the attention being paid to the youth, our young people are moving rapidly towards the future. With the Resolution No. 163 of the Cabinet of Ministers dated March 29, 2021, a regulation on measures to organize dual education was approved. Middle-level specialists play a crucial role in the development of the economy. There is a high demand for workers and specialists in the fields of production, industry, and services.